Investigating Childhood Fears during Preschool Period in terms of Child, Mother and Teacher Opinions - CENGİZ, ÖZGE (My University, 2018)
In this study, it is aimed to discover childhood fears of 60-72-month-old children through the opinions of preschool children, preschool teachers and mothers. Study group of the investigation consists of 52 participants; 18 children aged 60-72 months, 16 teachers and 18 mothers with preschool children, in Istanbul. An “Interview Form” which consists of 9 questions, was developed by the researchers. According to the findings, there are not significant differences in fear types among preschool children in different socioeconomic levels. In general, the most common fear types among all children are animals, robbery, natural events and nightmares. According to the mothers in lower and middle socioeconomic levels, children are mostly afraid of the dark and loneliness and to the mothers from upper socioeconomic level, they are afraid of strangers and unfamiliar settings, animals and loneliness. According to the teachers working in lower socioeconomic level schools, children are mostly afraid of animals; to the teachers from middle socioeconomic level schools, children are mostly afraid of the dark, strangers and unfamiliar settings; and according to the teachers working in high socioeconomic level schools, children are mostly afraid of separation, strangers and unfamiliar settings and loneliness.